Comparison of serum calcium, magnesium, phosphate, alkaline phosphatase, and vitamin D levels in children consuming reverse osmosis, non reverse osmosis, and high fluoride drinking water - H. M. Thippeswamy; Raghavendra Shanbhog; M. Nanditha Kumar; S. N. Prashanth; P. Smitha (Scientific Reports)
Abstract Water is vital for the human body. Due to concerns over tap water, preference for taste, and convenience, there has been increased consumption of reverse osmosis (RO) water. Various metal ions (e.g., magnesium, calcium, sodium) are essential for human growth and function. Evaluate and compare serum calcium, magnesium, phosphate, alkaline phosphatase, and vitamin D levels in children consuming RO, non-RO, and high-fluoride drinking water. This comparative study included children aged 9–13. Participants were divided into three groups: RO water drinkers, non-RO water drinkers, and those consuming high-fluoride water. A questionnaire gathered socio-demographic, medical, sunlight exposure, and including a validated food frequency questionnaire (FFQ) for nutrient intake. Water samples were analyzed per APHA guidelines for calcium, magnesium, phosphorous, fluoride, and TDS. Urine samples assessed calcium and creatinine, while automated chemistry analyzers measured calcium, phosphorous, and alkaline phosphatase. Vitamin D levels were analyzed using immunoassay. Participants across all age groups were evenly distributed among the three water type groups. Drinking water type significantly correlated with serum and ionic calcium, magnesium, alkaline phosphatase, and serum phosphate levels. Higher 24-h urine calcium and creatinine were found in the high-fluoride group. Regression analysis showed significant associations between drinking water calcium, magnesium, phosphate, TDS, and serum levels after adjusting for age, gender, socioeconomic status, and dietary intake. (serum calcium = β = 0.006, p < 0.001, serum magnesium = β = 0.002, p < 0.001,serum phosphate = β =  − 1.260, p = 0.016). Drinking water type impacts serum calcium, magnesium, phosphate, and alkaline phosphatase levels in children.